Populations at risk for severe or complicated Avian Influenza H5N1: a systematic review and meta-analysis. - Dominik Mertz; Tae Hyong Kim; Jennie Johnstone; Po-Po Lam; Michelle Science; Stefan P Kuster; Shaza A Fadel; Dat Tran; Eduardo Fernandez; Neera Bhatnagar; Mark Loeb (PLoS ONE)
Background Little is known about risk factors for severe outcomes in patients infected with H5N1 and no systematic review has been conducted. Understanding risk factors is an important step for prioritizing prophylaxis or treatment in the event of a pandemic. Objectives To systematically evaluate risk factors for severe outcomes in patients with avian influenza H5N1 infection. Data sources MEDLINE, EMBASE, CINAHL, GlobalHealth, and CENTRAL through March 2011. Eligibility criteria for selecting studies Observational studies of any design published in English, French, Spanish, German or Korean that reported on risk factor-outcome combinations of interest in participants with confirmed H5N1 infections. Outcomes considered included death, ventilator support, hospital and ICU admission, pneumonia, and composite outcomes. Study appraisal Risk of bias was assessed using the Newcastle-Ottawa scale (NOS). Results We identified 20 studies reporting on 999 patients infected with H5N1. The majority of studies (n = 14, 70%) were at intermediate risk of bias, i.e. 4-6 points on the NOS. Females were at increased risk of death (OR 1.75, 95% CI 1.27-2.44), while young age, in particular <5 years of age (OR 0.44, 95% CI 0.25-0.79 for death), was protective. Data on traditional risk factors was scarce and requires further studies. Another major limitation in the published literature was lack of adjustment for confounders. Interpretation Females were at increased risk for complications following H5N1 infection while young age protected against severe outcomes. Research on traditional risk factors was limited and is required.